Applying the rules in exponents, we can multiply binomials.
Expand and simplify :
Problem 1 :
(3x + 1) (3x + 2)
Solution :
(3x + 1) (3x + 2)
= 3x ⋅ 3x + 3x ⋅ 2 + 1 ⋅ 3x + 1 ⋅ 2
= 32x + (2+1) 3x + 2
= 32x + 3 ⋅ 3x + 2
= 9x + 3(x + 1) + 2
Expand and simplify :
Problem 2 :
(2x + 1) (2x + 5)
Solution :
(2x + 1) (2x + 5)
= 2x ⋅ 2x + 2x ⋅ 5 + 1 ⋅ 2x + 1 ⋅ 5
= 22x + 6 ⋅ 2x + 5
= 4x + 6 ⋅ 2x + 5
Problem 3 :
(5x - 2) (5x - 7)
Solution :
(5x - 2) (5x - 7)
= 5x ⋅ 5x - 5x ⋅ 7 - 2 ⋅ 5x + 2 ⋅ 7
= 25x - 9 ⋅ 5x + 14
Problem 4 :
(2x + 1)2
Solution :
(2x + 1)2
= (2x)2 + 2(2x)(1) + 12
= 22x + 2(x+ 1) + 1
= 4x + 2(x + 1) + 1
Problem 5 :
(3x + 2)2
Solution :
(3x + 2)2
= (3x)2 + 2(3x)(2) + 22
= 32x + 4(3x) + 4
= 9x + 4(3x) + 4
Problem 6 :
(4x - 7)2
Solution :
(4x - 7)2
= (4x)2 - 2(4x)(7) + 72
= 42x - 14(4x) + 49
= 16x - 14(4x) + 49
Problem 7 :
(3x + 1)2
Solution :
(3x + 1)2
= (3x)2 + 2(3x)(1) + 12
= 32x + 2(3x) + 1
= 9x + 2(3x) + 1
Problem 8 :
(3x - 8)2
Solution :
(3x - 8)2
= (3x)2 - 2(3x)(8) + 82
= 32x - 16(3x) + 64
= 9x - 16(3x) + 64
Problem 9 :
(5x - 3)2
Solution :
(5x - 3)2
= (5x)2 - 2(5x)(3) + 32
= 52x - 6(5x) + 9
= 25x - 6(5x) + 9
Problem 10 :
(x1/2 + 3) (x1/2 - 3)
Solution :
(x1/2 + 3) (x1/2 - 3)
= x1/2 ⋅ x1/2 - x1/2 ⋅ 3 + 3 ⋅ x1/2 – 3 ⋅ 3
= x - 9
Problem 11 :
(2x + 5) (2x - 5)
Solution :
(2x + 5) (2x - 5)
= 2x ⋅ 2x - 2x ⋅ 5 + 5 ⋅ 2x - 5 ⋅ 5
= 4x - 25
Problem 12 :
(x1/2 + x-1/2) (x1/2 + x-1/2)
Solution :
(x1/2 + x-1/2) (x1/2 + x-1/2)
= x1/2 ⋅ x1/2 + x1/2 ⋅ x-1/2 + x-1/2 ⋅ x1/2 + x-1/2 ⋅ x-1/2
= x – x-1
= x – 1/x
Problem 13 :
(x + 3/x)2
Solution :
(x + 3/x)2
= x2 + 2(x)(3/x) + (3/x)2
= x2 + 6 + 9/x2
Problem 14 :
(ex – e-x)2
Solution :
(ex – e-x)2
= (ex)2 – 2(ex)(e-x) + (e-x)2
= e2x – 2 + e-2x
Problem 15 :
(3 – 2-x)2
Solution :
(3 – 2-x)2
= 32 – 2(3)(2-x) + (2-x)2
= 9 – 6(2-x) + 4-x
= 9 – (6/2x) + (1/4)x
May 21, 24 08:51 PM
May 21, 24 08:51 AM
May 20, 24 10:45 PM